Cloud-Based Data Integration and Machine Learning Applications in Biopharmaceutical Supply Chain Optimization - Mahesh Recharla; Subrahmanyasarma Chitta (Kurdish Studies, 2022)
Cloud-based data integration and machine learning applications are becoming increasingly popular in many industries because they provide a great deal of flexibility for managing different types of specialized data. Cloud platforms can now handle large volumes of diverse data rapidly, and they support a variety of storage services and machine learning applications for big data analytics. Creating advances in reliability, speed, and robustness on a secure platform, they permits the development of powerful enhancements to business functions. In the rigorous regulatory environment of biopharmaceutical supply chain operations, the value of cloud-based services in data integration process efficiency and capability for machine learning-based analytics is of significant importance. This text explains the use of cloud-based data integration and machine learning applications in the biopharmaceutical supply chain planning and management area, where significant but underutilized data resources exist. The use of production planning-related data can yield significant strategic and tactical advantages in reliability, responsiveness, and cost control, offering substantial commercial benefits. A secure cloud-based data integration platform can enable a high level of capability, efficiency, validation, and transparency for use in biopharmaceutical regulatory environments. The scope can increase the potential for both continuous improvement and benefits from operational analytical techniques and can enhance trust at all levels of planning and operations. Regulatory requirements for biopharmaceutical data acquisition, processing, and analysis can be addressed using a secure, high-capability platform, repository, and large-scale machine-learning application technologies. Consequently, a high-power platform methodology can be prepared for use in a variety of upgrade and value-added applications with a broad range of operational reach, which traditional internal capability cannot provide efficiently.